2020
DOI: 10.1039/c9nr08424j
|View full text |Cite
|
Sign up to set email alerts
|

Heritable nanosilver resistance in priority pathogen: a unique genetic adaptation and comparison with ionic silver and antibiotics

Abstract: A priority pathogen is capable to evolve stable resistance characteristics that still manifest after discontinuation of the nanosilver exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
2
39
1
Order By: Relevance
“…Over several years, a growing number of studies have been published describing the phenomenon of resistance in bacterial species in response to different forms of silver agents, including NAg. Silver resistance has been reported in A. baumannii and many other important pathogenic bacteria (Gupta et al, 1999;Gunawan et al, 2013;Muller and Merrett, 2014;Panáček et al, 2018;Hosny et al, 2019;Valentin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over several years, a growing number of studies have been published describing the phenomenon of resistance in bacterial species in response to different forms of silver agents, including NAg. Silver resistance has been reported in A. baumannii and many other important pathogenic bacteria (Gupta et al, 1999;Gunawan et al, 2013;Muller and Merrett, 2014;Panáček et al, 2018;Hosny et al, 2019;Valentin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of efflux pumps that can extrude metal ions and antibiotics represents the most conspicuous example of this [71]. The increased abundance of efflux pump genes in soil and water environments under NP exposure has been proven by several studies [14,15,35,56,61,62]. As stated above, some efflux pumps of the RND family are known to export antibiotics in P. aeruginosa [83].…”
Section: Arming the Enemy: Metallic Nps May Act As Pressure That Co-smentioning
confidence: 92%
“…Indeed, overexpression of genes encoding ROS scavenging systems have been demonstrated in E. coli, B. subtilis, and P. aeruginosa PAO1 exposed to Ag-NPs, Al2O3-NPs, and Cd-QDs, respectively [56,57,64], and have been correlated with a better capacity to tolerate prolonged exposure to Ag-NPs [52]. Furthermore, recent work carried out by Valentin and collaborators [14] reported that Ag-NP resistance evolved in S. aureus was associated with mutations in genes involved in nucleotide synthesis and oxidative stress defenses.…”
Section: Bacterial Resistance Mechanisms Towards Metallic Nanoparticlesmentioning
confidence: 97%
See 2 more Smart Citations